Pelatihan Digital Marketing Sebagai Upaya Menumbuhkan Jiwa Entrepreneur Pada Siswa SMKS Penerbangan SPN Dirgantara Batam - Yulia, Yulia; Sembiring, Diamon; Butar Butar, Resti; Karnadi, Very (PUAN INDONESIA, 2024)
Digital marketing is the process of marketing and promoting a brand, product or service which is carried out using digital media and requires an internet network for its activities. Digital marketing is a new way for a company or businessman to reach consumers. To carry out digital marketing activities, you need an entrepreneur. The term entrepreneur is no longer foreign to today's technology-based world. An entrepreneur is an individual who can create a new business, is willing to bear most of the risks, and in return can enjoy most of the profits. The process of setting up an entrepreneur's business is called entrepreneurship or entrepreneurship. Students can access a wider audience by using digital marketing tools and students can reach a wider and global audience. By using online platforms, entrepreneurs can reach potential customers from various locations. The aim of this service activity is as the way to Improve the Enterpreuneur Spirit of SMKS Penerbangan SPN Dirgantara Students. The benefits obtained by students from service activities are that students can apply cost efficiency in product promotion, students can create interesting personal content from the product brands they design, students can think systematically and have entrepreneurship skills and students are able to adapt to the external environment.